PKM Musyawarah Guru Mata Pelajaran (MGMP) Kimia Kabupaten Donggala Dalam Penyusunan Dan Publikasi Karya Ilmiah - Rahmawati, Sitti; Hamzah, Baharuddin (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2020)
Partners of this service activity are Chemistry teachers who are members of the Donggala District Teacher Meeting (MGMP). The problems faced by the partner groups, including members of the Chemistry Subject Teacher Conference (MGMP), still experienced difficulties in: a) designing the implementation of CAR in the learning process (how to identify problems, select and formulate topics and titles for classroom action research, b) apply models learning and learning media in the implementation of CAR and how to collect data that is appropriate and efficient, c) scientific reading tracing techniques, especially in the form of journals to be used as a reference for writing (literature search), d) analyzing and interpreting data obtained during research, e) making instruments research, especially CAR and data presentation techniques, f) writing techniques and submitting article manuscripts to scientific journals and the lack of resource persons. The purpose of this PKM is to provide assistance and training for chemistry teachers, especially those who are members of the Donggala District Chemistry MGMP in preparing research reports and articles that meet the requirements for publication in scientific journals, preceded by training in processing and analyzing research data.. The method used in this PKM activity is conducting training and workshops on the implementation of CAR, making research instruments, processing and analyzing research data. Furthermore, they will assist partners in preparing the PTK report and its publication and can process the PTK research data into the form of scientific paper articles and published in ISSN journals or at national level scientific seminars. The implementation of workshops and training on the preparation and publication of scientific papers is very beneficial for the Chemistry MGMP of Donggala Regency which has had difficulty meeting the requirements for promotion in the field of writing scientific papers. In the application of the practice of writing articles, three members of the Chemistry MGMP of Donggala Regency, have made classroom action research reports, processed data and wrote in scientific articles, and temporarily reviewed them for publication in interactive journals.